2014
DOI: 10.1016/j.physa.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying randomness in protein–protein interaction networks of different species: A random matrix approach

Abstract: We analyze protein-protein interaction networks for six different species under the framework of random matrix theory. Nearest neighbor spacing distribution of the eigenvalues of adjacency matrices of the largest connected part of these networks emulate universal Gaussian orthogonal statistics of random matrix theory. We demonstrate that spectral rigidity, which quantifies long range correlations in eigenvalues, for all protein-protein interaction networks follow random matrix prediction up to certain ranges i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…These networks have already been shown to follow universal RMT predictions of GOE statistics [53]. We concentrate here on the occurrence of high degeneracy at the zero eigen value.…”
Section: Resultsmentioning
confidence: 93%
“…These networks have already been shown to follow universal RMT predictions of GOE statistics [53]. We concentrate here on the occurrence of high degeneracy at the zero eigen value.…”
Section: Resultsmentioning
confidence: 93%
“…It was found that spectra of such networks were governed by characteristic features of the underlying networks. The spectral density of an array of real-world networks exhibit triangular structure, owing to their underlying scale-free topology [28,47,48].…”
Section: Spectral Densitymentioning
confidence: 99%
“…As discussed, for scale-free networks generated using preferential attachment mechanism, it fails to provide a quantitative measure of actual degeneracy observed in real world networks [41], indicating the contribution from other factors. Scale-free behaviour or sparseness of real world networks have been argued out to be other reasons responsible for degeneracy at the zero eigenvalues [40,41,47].…”
Section: Degenerate Eigenvaluesmentioning
confidence: 99%
“…In such a scenario, one settles for a model that captures the statistical properties of the energy spectrum. RMT finds extensive applications in the statistical studies of various complex systems such as quantum chaotic systems, complex nuclei, atoms, molecules, disordered mesoscopic systems [16][17][18][19][20][21][22][23][24], atmosphere [25], financial applications [26], complex networks [27], societal networks [28], network forming systems [29,30], amorphous clusters [31][32][33][34], biological networks [35], protein networks [36,37], and cancer networks [38] etc. In recent years, RMT has also been applied towards brain network studies in studying universal behavior of brain functional connectivity and has been effective in detecting the differences in resting state and visual stimulation state [39,40].…”
Section: Introductionmentioning
confidence: 99%